Friends, Foes, and Fringe: Norms and Structure in Political Discussion Networks - Kelly, John; Fisher, Danyel; Smith, Marc (Online Deliberation: Design, Research, and Practice, 2009)
The Internet offers numerous modes of online discussion, with many different forms of control. Some empower one person to control agenda and content. Blogs are perhaps the most extreme version of this, in which one person contributes most of the content and can censor, delete or disallow feedback from others. Moderated discussion groups offer a less extreme version of such control, in which discussants are expected to carry on the majority of the discourse. Still other forums allow collaborative, group controls. Slashdot is a premiere example, in which users deploy randomly assigned rating points to grade particular comments up or down, making them more or less visible to subsequent readers (Lampe 2004). If we envision a continuum of control, from the dictatorial blog on the one hand, through the constitutional monarchy of moderated discussion, to the kind of Athenian democracy (power being randomly assigned to ‘citizens’ for short durations) of Slashdot, the extreme anarchic pole is perhaps best represented by Usenet (Pfafenberger 2003).
The book is availale at http://odbook.stanford.edu/